Pengaruh non performing loan, biaya operasional pendapatan operasional, current adequacy ratio, dana pihak ketiga terhadap return on assets pada Bank BUMN - Inayah, Alifah Dienul (Management Journal and Economic Review, 2022)
This population consists of 4 state-owned banks in Indonesia. The data analysis technique is the validity and reliability test, then continued with the classical assumption test, which include normality, multicollinearity, and heteroscedasticity, t-test and F test, and calculation of correlation coefficients, multiple linear regression and determination. The results of this study NPL has no significant effect on ROA, BOPO has a significant effect on ROA, CAR has no significant effect on ROA, and DPK has no significant effect on ROA.